Brief research report: impact of vaccination on antibody responses and mortality from severe COVID-19 - Adhikari, Bindu; Bednash, Joseph S.; Horowitz, Jeffrey C.; Rubinstein, Mark P.; Vlasova, Anastasia N. (Frontiers in Immunology, 2024)
Introduction: While it is established that vaccination reduces risk of hospitalization, there is conflicting data on whether it improves outcome among hospitalized COVID-19 patients. This study evaluated clinical outcomes and antibody (Ab) responses to severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection/vaccines in patients with acute respiratory failure (ARF) and various comorbidities. Methods: In this single-center study, 152 adult patients were admitted to Ohio State University hospital with ARF (05/2020 -11/2022) including 112 COVID-19-positive and 40 COVID-19negative patients. Of the COVID-19 positive patients, 23 were vaccinated for SARS-CoV-2 (Vax), and 89 were not (NVax). Of the NVax COVID-19 patients, 46 were admitted before and 43 after SARS-CoV-2 vaccines were approved. SARS-CoV-2 Ab levels were measured/analyzed based on various demographic and clinical parameters of COVID-19 patients. Additionally, total IgG4 Ab concentrations were compared between the Vax and NVax patients.Results: While mortality rates were 36% (n=25) and 27% (n=15) for non-COVID-19 NVax and Vax patients, respectively, in COVID-19 patients mortality rates were 37% (NVax, n=89) and 70% (Vax, n=23). Among COVID-19 patients, mortality rate was significantly higher among Vax vs.NVax patients (p=0.002). The Charlson's Comorbidity Index score (CCI) was also significantly higher among Vax vs. NVax COVID-19 patients. However, the mortality risk remained significantly higher (p=0.02) when we compared COVID-19 Vax vs. NVax patients with similar CCI score, suggesting that additional factors may increase risk of mortality. Higher levels of SARS-CoV-2 Abs were noted among survivors, suggestive of their protective role. We observed a trend for increased total IgG4 Ab, which promotes immune tolerance, in the Vax vs. NVax patients in week 3.Although our cohort size is small, our results suggest that vaccination status of hospital-admitted COVID-19 patients may not be instructive in determining mortality risk. This may reflect that within the general population, those individuals at highest risk for COVID-19 mortality/immune failure are likely to be vaccinated. Importantly, the value of vaccination may be in preventing hospitalization as opposed to stratifying outcome among hospitalized patients, although our data do not address this possibility. Additional research to identify factors predictive of aberrant immunogenic responses to vaccination is warranted.